Hoogmoed as motief in die profetiese uitsprake teen nie-Israelitiese volke - Boshoff, F. J. (Hervormde teologiese studies, 1987)
Pride as motif in the prophecies against foreign nations Pride is a common motif in the prophecies against foreign nations. The concept of pride in these prophecies must be understood in a theological context, i.e. that everything has its place and function within the world order. Pride represents a short-circuit within this world order. It is God who acts against pride, every time. Significantly, pride as a motif appears especially in times of exile.